Demand Analysis of Beef in Indonesia - Amalia, Dwi Cahya; Badriah, Lilis Siti; Sambodo, Herman (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
Abstract This study aims to analyze the influence of beef prices, substitute goods prices (mutton and chicken meat), complementary goods prices (chicken eggs and rice), and per capita income on the demand for beef in Indonesia. Additionally, it seeks to assess the elasticity of beef demand within the country. Employing multiple linear regression analysis on secondary data collected over a 30-year period (1990-2022), the results reveal that: (1) The variables—beef price, mutton price, chicken meat price, chicken egg price, rice price, and per capita income—significantly affect the demand for beef in Indonesia. Specifically, the price of chicken eggs exhibits a significant negative effect, while per capita income shows a significant positive effect on beef demand. (2) The cross-price elasticity of demand between beef and chicken meat is -0.09, indicating inelasticity, and the income elasticity of demand is 0.52, also indicating inelasticity.